Meta-Analysis of the Use of Augmented Reality Applications in Science Teaching - Zeynel Abidin Yilmaz; Veli Batdi (Universitas Pendidikan Indonesia, 2021)
This study aims to reach the meta-analysis data by analyzing the augmented reality (AR) applications used in Science Education. The search was conducted on specific databases considering the studies carried out between 2000 and 2019 years. While collecting data, inclusion criteria were considered. After searching the related databases, 24 studies were reached. Based on the random-effects model, the study results revealed that the ES value was g = 0.602, which means a medium size in the meta-analysis process according to Thalheimer and Cook's (2002) calculation level. Furthermore, z-test calculations conducted to reveal the statistical significance were found to be z = 4.989, which showed that AR applications had a significant effect on science learning. In this context, it is thought that this technological design, which offers a positive contribution to science education, allows interacting with animations or simulations simultaneously without breaking away from the real world and will serve as a model for future studies.